A pioneer of Australian paediatrics: Dr Henry Edward Brown (1858–1931). (13th November 2014) - Isles, Alan F; Roper, Peter; Pearn, John H
Abstract The emergence of paediatrics as a specialty in Australian medicine dates from the last two decades of the 19th century. Among the pioneers of pre‐Federation paediatrics, we include Dr Henry Edward Brown (1858–1931), an Irish‐born physician and surgeon who became the first paediatrician to practise in the northern half of the Australian continent. In 1885, he was appointed as the medical superintendent of the Rockhampton Children's Hospital, itself a pioneer institution in the care of sick and injured children. Dr H.E. Brown also served as medical officer of health concurrently in three Queensland shires. He was a leader in the literary and sporting life of the busy port town of Rockhampton and a scholar and significant philanthropist in the domain of French literature. His life was and remains an exemplar of a class of pre‐Federation paediatricians who established the ethos of clinical and societal service, which remains as a core feature of the speciality discipline of paediatrics in the 21st century.